BUILDING CONSUMER SATISFACTION TO IMPROVE CONSUMER TRUST THROUGH SERVICE QUALITY AND CONSUMER EXPERIENCE IN JNE PEKANBARU - Junaedi, Achmad Tavip; Wijaya, Evelyn; Manullang, Megawati (Jurnal Aplikasi Manajemen, 2020)
e-Commerce is growing and influencing the business world. Service quality and consumer experience have an influential role to provide consumer satisfaction and trust. This study aims to understand and analyze the influence of service quality and consumer experience on consumer satisfaction and consumer trust in JNE Pekanbaru. The population in this study is all consumers who have used JNE logistics services in Pekanbaru. The sampling used an accidental sampling technique with 150 respondents. The researchers utilized path analysis techniques with the PLS program. The results show service quality and consumer experience had a significant positive effect on consumer satisfaction and trust. Consumer satisfaction encourages the creation of consumer trust in JNE of Pekanbaru. Therefore, next researches are expected to be able to explore other variables such as customer value, customer relationship management, and other variables suspected of affecting consumer satisfaction and consumer trust.